Loss of Vision Dominance at the Preresponse Level in Tinnitus Patients: Preliminary Behavioral Evidence - Li, Zhicheng; Gu, Ruolei; Qi, Min; Cen, Jintian; Zhang, Shuqi; Gu, Jing; Zeng, Xiangli; Chen, Qi (Frontiers in Neuroscience, 2019)
At present, the mechanisms underlying changes in visual processing in individuals with tinnitus remain unclear. We therefore investigated whether the vision dominates of individuals with tinnitus disappear at the preresponse level through behavioral study. A total of 38 individuals with tinnitus and 31 healthy controls completed a task in which they were asked to attend to either visual or auditory stimuli while ignoring simultaneous stimulus inputs from the other modality. We manipulated three levels of congruency between the simultaneous visual and auditory inputs: congruent (C), incongruent at the preresponse level (PRIC), and incongruent at the response level (RIC). Thus, we differentiated the cross-modal conflict explicitly into the preresponse (PRIC > C) and response (RIC > PRIC) levels. The results revealed no significant difference in the size of the preresponse level conflict between the auditory attention and visual attention conditions in tinnitus group. In brief, the preresponse level of individuals with tinnitus showed a loss in vision dominates. This may be due to the reduced interference of visual information in auditory processing.